Analysis and evaluation of modular E‐shaped stator switched reluctance machines employing segmented and conventional rotor topologies. Issue 9 (1st November 2016) - Ding, Wen; Hu, Yanfang; Fu, Haigang; Chen, Qingsong
Abstract : Switched reluctance machines (SRMs) with modular or segmented structures normally have light weight, low cost, easily manufactured and improved fault‐tolerance capability. In this study, two novel three‐phase modular SRMs (MSRMs) with the same E‐shaped stator modules and different rotor topologies, namely, segmented rotor and conventional rotor are evaluated and compared. The basic machine topologies and simplified magnetic equivalent circuit (MEC) are presented first. The static electromagnetic characteristics of two MSRMs such as flux distribution, phase flux linkage and inductance, electromagnetic torque, and so on, are computed and compared by three‐dimensional finite‐element analysis. Then, the dynamic performances including steady state and transient operations of two MSRM drives are evaluated and compared. The corresponding predictions and comparisons indicate that the segmented rotor topology has less iron consumption, higher torque density and power density and lower torque ripple, which is preferred for the three‐phase MSRMs. Finally, two MSRM prototypes with segmented rotor and conventional rotor are manufactured and tested for experimental verification and comparison. The experimental results of static flux linkage, steady state and transient performances of two MSRM drives are presented and compared, which verify the analytical MEC model, finite element analysis and the corresponding predictions.